Use of a Pedicled Vascularized Ulnar Nerve as a Long Graft for Complete Brachial Plexus Palsy in Adults to Restore Elbow Flexion: Should this Practice Continue? - Echalier, Camille; Goubier, Jean Noël (Journal of Brachial Plexus and Peripheral Nerve Injury, 2025)
Restoring elbow flexion is a priority in adults with complete brachial plexus palsy. If the nerve root is not avulsed, a graft can be placed between the existing root and the musculocutaneous nerve. The aim of this study was to evaluate the outcomes of using vascularized ulnar nerve grafts in this context. Our case series consisted of 17 male and 3 female patients (mean age of 31 years) presenting complete brachial plexus palsy after a motorcycle accident. A graft at the C5 or C6 root on the musculocutaneous nerve was done in all patients using a pedicled vascularized ulnar nerve to restore elbow flexion at a mean of 5 months after the accident. At a mean follow-up of more than 3 years, elbow flexion was graded as M4 in six patients and between M0 and M2 in the other 14 patients on the Medical Research Council scale. None of the patients had M3 strength. While the results of long grafts using a vascularized ulnar nerve are disappointing in this case series, they are consistent with previous publications. Encouraging results have only been reported with short grafts (<10 cm), which can rarely be used with supraclavicular lesions. For this reason, we currently prefer using a sural nerve graft or nerve transfer, when possible, to restore elbow flexion in adult patients with brachial plexus injuries.
Keywords: brachial plexus; nerve graft; vascularized ulnar nerve; allograft